INSIDENSI PENYAKIT KARAT PADA KACANG MERAH (Vigna angularis (Willd) Ohwi& H.Ohashi) DI KABUPATEN MINAHASA - Wati Husain; Guntur S.J. Manengkey; Henny V.G. Makal; Johanna M. Paath (Universitas Sam Ratulangi, 2013)
ABSTRACTThis study aims to determine the symptoms and the incidence of rust disease on red beans in Minahasa Regency. The research was conducted in July to Oktober 2012 in the village of Tonsewer, Toured and Tumaratas. Continued research in the Laboratory of Microbiology and Plant Diseases, Faculty of Agriculture, University of Sam Ratulangi Manado, to observe microscopic rust disease symptoms on kidney beans. The method used was a survey method by making an incision on the diagonal red bean plant sample plots with a size of 2 x 2 m and subsequent rust disease incidence was observed in these plants. Based study showed that the rust disease caused by a Uromyces sp. fungus that has synctoms on the upper and bottom leaf surface of the small spot form with the color rather pale, sligthly up (stand). In general these tiny spots surrounded by a chlorotic part, although there are also the only form of brown spots. Incidence of the disease increases with age of the plant until near harvest and the fourth observation in the village of Tonsewer 47.06 %, village of Toure 46.08 % and village of Tumaratas 47.06 %.Keyword: Imcidence of rust disease on red beans, Uromyces sp.